Cardiovascular risk in a school population with excess weight - Pajuelo-Ramírez, Jaime (2020)
Objective. To determine the cardiovascular risk factors in overweight schoolchildren and to measure their association with sociodemographic variables. Methods: Cross-sectional, analytical study. 2001 female schoolchildren from 6 to 17 years of age from an Educational Center in Metropolitan Lima were surveyed. The Body Mass Index was used for the diagnosis of excess weight (overweight between 85 and 95p and obesity ≥ 95p) and the Waist Circumference for abdominal obesity (≥ 90p). HOMA-I for insulin resistance (≥ 3,16) and for lipid abnormalities: total cholesterol (≥ 200 mg / dL), low HDL-C (≤ 40 mg/dL), high LDL-C (≥ 130 mg / dL), non-HDL C (≥ 145 mg / dL) and triglycerides (≥ 100 and 130 mg / dL) for girls younger than 9 and 10 to 19 years old, respectively. Results: Excess weight occurred mainly in schoolgirls aged 10 to 17 years, in those who were born with more than 2500 gr, with more than one family history, with exclusive breastfeeding and in those whose mothers had no instruction. The most frequent lipid alterations were hypertriglyceridemia and low HDL-C. 82% had dyslipidemia and 55,4% of obese patients had insulin resistance (IR). Abdominal obesity was associated with family history and mother’s instruction. Conclusion: Four out of five girls with excess weight presented at least one alteration of the lipids. One in two obese women had IR.